2013
DOI: 10.1074/jbc.m113.512731
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability of Inositol 1,3,4,5,6-Pentakisphosphate 2-Kinase (IPK1) Dictates Its Substrate Selectivity

Abstract: Background:The phosphate profile of the inositol phosphate (IP) substrate defines inositol 1,3,4,5,6-pentakisphosphate 2-kinase (IPK1) specificity. Results: IP substrate specificity is linked to IPK1 stability. Conclusion: IPK1 employs a mechanism of IP-induced stabilization to selectively recognize IP 5 . Significance: The IP recognition mechanism of IPK1 can be exploited to selectively target IPK1 for the study of higher IPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The first helical segment (N-I) harbors α1, equivalent to the helix αC characterized in all protein kinases, whereas the second one (N-II) is a specific insertion different in every IPK subfamily. A role of this region for substrate binding in the IP 5 2-K subfamily has been previously reported by others ( 29 ) and by us ( 25 , 27 ). Regarding the C-lobe, it also presents a β-sheet core formed by five antiparallel β-strands (β6–β10).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The first helical segment (N-I) harbors α1, equivalent to the helix αC characterized in all protein kinases, whereas the second one (N-II) is a specific insertion different in every IPK subfamily. A role of this region for substrate binding in the IP 5 2-K subfamily has been previously reported by others ( 29 ) and by us ( 25 , 27 ). Regarding the C-lobe, it also presents a β-sheet core formed by five antiparallel β-strands (β6–β10).…”
Section: Resultssupporting
confidence: 77%
“…2 C ). The role of the Arg-100 equivalent in At IP 5 2-K (Arg-130) has been largely argued, and an implication in substrate binding and triggering of a productive protein conformation has been proposed ( 27 , 29 , 30 ). Unfortunately, a construct prepared for the R100A m IP 5 2-K mutant did not show expression in the soluble fraction.…”
Section: Resultsmentioning
confidence: 99%
“…The validity of our interpretation for purpurogallin is supported by the observation that the enzyme is found in the 'closed' conformation previously only observed when in Table 2), while the RMSDs between the inositide-and nucleotide-coordinating residues of the two structures are 0.52 Å and 0.35 Å, respectively (Supporting Information Table 4). Additionally, Gly254 and Glu255 (strand L3) form interactions respectively, with Arg130 and Trp129 (helix α6), interactions serving as hallmark features of the 'fully-closed' form of the enzyme 14,15 . Significantly, all published inositide ligand-free structures (i.e.…”
Section: Ternary Structure Of Atip5 2-k With Purpurogallin and Adpmentioning
confidence: 99%
“…17 We rationalized that a fluorescent-tagged inositol pentakisphosphate, 2-FAM-InsP 5 18 may, in contrast, work directly as an active-site ligand for inositol phosphate kinases that accom- modate inositide and nucleotide cosubstrates in relatively large (volume) active sites or in enzymes such as inositol pentakisphosphate 2-kinase which show ligand-induced folding motions that accompany catalysis. 14,15 To date, this and similar molecules have been used only as ligands of inositol phosphate-binding proteins such as the IP 3 receptor 19 and the histone deacetylase, HDAC3, which binds D-Ins (1,4,5,6)P 4 between itself and its cognate partner. 20 We further rationalized that IP5 2-K, which lacks phosphatase activity, 21 would, in the absence of nucleotide, be unable to dephosphorylate the fully substituted inositol ring of the probe or phosphorylate it.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This finding showed its particular features, the most striking one is the presence of a notably helical scaffold inserted into the IPK core that serves to bind the inositide substrate. Later structural studies showed a possible conformational change accompanying IP 5 2-K catalysis [14][15][16][17]. However, the structure of mammal IP 5 2-K remains unknown, in spite of its reported interesting roles.…”
Section: Introductionmentioning
confidence: 95%